A model to simulate the cyclic axil compressive behaviour of rc columns confined with CFRP sheets - Varma, Rajendra (2008)
In the present work a constitutive model to predict the cyclic axial compressive behavior of RC columns confined with CFRP is proposed. This model was implemented in a FEM-based computer program, able to simulate the material nonlinear behavior of reinforced concrete frame structures. The performance of the developed model is assessed using results obtained from experimental tests.